2020
DOI: 10.32872/cpe.v2i2.2623
|View full text |Cite
|
Sign up to set email alerts
|

The effect of television and print news stories on the nocebo responding following a generic medication switch

Abstract: Background Following a nationwide switch to a generic antidepressant, a series of negative media stories publicised the experiences of some patients having side effects following the switch. This occurred first in print media and five months later it occurred again in television news. In this study we examined the effect of television news stories compared to print stories on adverse drug reaction reporting. We also examined the change in reporting rate of specific side effects mentioned in the TV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…To account for a potential confound of increased headache presentations by higher vaccination rates against COVID-19, weekly vaccination rates as monitored by the RKI were obtained from Github 14 for the city of Essen and the federal state of North Rhine-Westphalia (NRW), where Essen is located. We also screened data of ER reports during the time of "booster" vaccinations (= third vaccination against COVID-19), which was approximately 9 months after our main time range of interest.…”
Section: Data Collection and Processingmentioning
confidence: 99%
See 2 more Smart Citations
“…To account for a potential confound of increased headache presentations by higher vaccination rates against COVID-19, weekly vaccination rates as monitored by the RKI were obtained from Github 14 for the city of Essen and the federal state of North Rhine-Westphalia (NRW), where Essen is located. We also screened data of ER reports during the time of "booster" vaccinations (= third vaccination against COVID-19), which was approximately 9 months after our main time range of interest.…”
Section: Data Collection and Processingmentioning
confidence: 99%
“…nocebo effects (14). Third, surveys investigating social media consumption showed that the number of posts seen about COVID-19 side effects, and the severity of symptoms conveyed in the posts, were predictive of the severity of side effects experienced after vaccination, indicating a "dose-dependent" effect of media exposure (15,16).…”
Section: Comparison With the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Newspaper coverage of side effects was also found to be associated with an increase in adverse event reports from the HPV vaccination ( Faasse et al, 2017 ). Media coverage discussing side effects from a generic antidepressant was associated with an increase in adverse event reporting, with television increasing the reporting rate by more than 210% compared to print media ( MacKrill et al, 2019 ; MacKrill et al, 2020 ). Recently, the discussion of rare COVID-19 vaccine side effects in the media resulted in increased reporting of cardiac complaints, which were likely self-diagnosed ( MacKrill, 2023 ).…”
Section: Health Scare Spreadmentioning
confidence: 99%
“…In one study, the Centers for Disease Control and Prevention found that 64% of respondents were regular watchers of television, and 67% of regular daytime drama viewers reported learning something new about a health issue or disease from a television show in the previous 6 months (19). Television is a preferred source of medical information for many members of the public (20,21), including some patients with gout (22), and compared to print media, television depictions can have a strong influence on patient-reported symptoms (23,24).…”
Section: Introductionmentioning
confidence: 99%